Effect of SLC30A8 rs13266634 Genetic Polymorphism with Diabetic Nephropathy Patients - Kadhim, Noorhan E.; Hoidy, Wisam Hindawy (Central Asian Journal of Medical and Natural Science, 2024)
Diabetic nephropathy is a pathological disease that is commonly observed in persons with diabetes. The purpose of this research was to compare the effects of the SLC30A8 rs13266634 gene polymorphism on people with and without diabetic nephropathy. The study comprised 170 patients, aged 40 to 75, who were admitted to the dialysis unit at the Al-Diwaniyah Teaching Hospital in Iraq in 2021 and 2022. There is a connection between SLC30A8 gene polymorphisms and diabetic nephropathy, according to the results of a study looking at the interaction between comorbid diseases and patients with the disease. Particularly, we discovered that individuals with the C allele of T/C (OR = 0.509, 95% Cl = 0.307- 0.843, p-value = 0.008 < 0.05), the TC genotype of T/C (OR = 0.280, 95% Cl = 0.118- 0.665, p-value = 0.003 < 0.05), and the TC & CC genotype had higher odds of infection with DN compared to the TT genotype (OR = 0.391, 95% Cl = 0.203- 0.756, p-value = 0.005 < 0.05).